2007
DOI: 10.1063/1.2429729
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of single crystal Zn1−xMgxO nanorods—Experimental and theoretical studies

Abstract: Structural and optical properties of single crystal Zn 1−x Mg x O nanorods ͑0 Յ x Յ 0.17͒ are studied experimentally and theoretically. Structural analyses indicate that the nanorods grown on Si substrates are oriented in the c-axis direction and the nanorods possess the single-crystalline hexagonal structure with the Mg incorporated within the ZnO nanorods by means of substituting Zn. A blueshift of the near-band edge emission in the photoluminescence spectra by increasing Mg content is observed. Two distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…The observed nanorods were randomly oriented which could be due to lack of lattice compatibility between the quartz surface and ZnO/MgO multilayers. Chang et al [15] and Heo et al [16] have reported maximum Mg content of 17% in MOCVD and MBE deposited ZnMgO nanorods. However in our case, we observed ZnMgO nanorods with Mg content up to 35% giving rise to large band gap tuning which prospects its application in solar blind photodetectors.…”
Section: Structural Propertiesmentioning
confidence: 98%
“…The observed nanorods were randomly oriented which could be due to lack of lattice compatibility between the quartz surface and ZnO/MgO multilayers. Chang et al [15] and Heo et al [16] have reported maximum Mg content of 17% in MOCVD and MBE deposited ZnMgO nanorods. However in our case, we observed ZnMgO nanorods with Mg content up to 35% giving rise to large band gap tuning which prospects its application in solar blind photodetectors.…”
Section: Structural Propertiesmentioning
confidence: 98%
“…Among them, the zinc oxide nanostructures received much attention for being room-temperature lasers, light-emitting diodes, transparent fieldeffect transistors, ultraviolet photodetectors, and solar cells. Especially, the ZnO nanorods gain increasing interest since they offer a unique opportunity for fabrication of nanoscale optoelectronic devices such as field-emission device [1], field-effect transistor [2], and light-emitting device [3]. Although various potential applications for the ZnO nanorods have been proposed, the experimental understanding on the optical anisotropy of the ZnO nanocrystal with different crystal axes is still rather incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…However, the features in the spectra from the Zn 1À x Mg x O films are less distinct than those from the single crystal ZnO. This could be the result of defects, a reduction in the number of unoccupied O 2p-derived states, or an increase in the number of electrons within O ions [30,31]. An increase in the number of electrons in O ions after Mg doping is expected since Mg has a significantly smaller electronegativity.…”
Section: Resultsmentioning
confidence: 85%
“…An increase in the number of electrons in O ions after Mg doping is expected since Mg has a significantly smaller electronegativity. More electrons are therefore transferred from Mg to the O 2p states, and the ionic character of the Zn 1À x Mg x O alloys is increased [30,31].…”
Section: Resultsmentioning
confidence: 98%